Long-term sialidase-specific immune responses after natural infection with cholera: Findings from a longitudinal cohort study in Bangladesh - Chowdhury, Fahima; Akter, Afroza; Bhuiyan, Taufiqur Rahman; Biswas, Rajib; Firoj, Md. Golam; Tauheed, Imam; Harris, Jason B.; Larocque, Regina C.; Ross, Allen G.; McMillan, Nigel A. J.; Charles, Richelle C.; Ryan, Edward T.; et al. (Frontiers in Immunology, 2022)
Background: Immune responses that target sialidase occur following natural cholera and have been associated with protection against cholera. Sialidase is a neuraminidase that facilitates the binding of cholera toxin (CT) to intestinal epithelial cells. Despite this, little is known about age-related sialidase-specific immune responses and the impact of nutritional status and co-infection on sialidase-specific immunity. Methods: We enrolled 50 culture-confirmed Vibrio cholerae O1 cholera cases presenting to the icddr,b Dhaka hospital with moderate to severe dehydration. We evaluated antibody responses out to 18 months (day 540) following cholera. We assessed immune responses targeting sialidase, lipopolysaccharide (LPS), cholera toxin B subunit (CtxB), and vibriocidal responses. We also explored the association of sialidase-specific immune responses to nutritional parameters and parasitic co-infection of cases. Results: This longitudinal cohort study showed age-dependent differences in anti-sialidase immune response after natural cholera infection. Adult patients developed plasma anti-sialidase IgA and IgG responses after acute infection (P<0.05), which gradually decreased from day 30 on. In children, no significant anti-sialidase IgA, IgM, and IgG response was seen with the exception of a late IgG response at study day 540 (p=0.05 compared to adults). There was a correlation between anti-sialidase IgA with vibriocidal titers, as well as anti-sialidase IgA and IgG with anti-LPS and anti-CtxB antibody responses in adult patients, whereas in children, a significant positive correlation was seen only between anti-sialidase IgA and CtxB IgA responses. Stunted children showed significantly lower anti-sialidase IgA, IgG, and IgM antibody responses and higher LPS IgG and IgM antibody responses than healthy children. The anti-sialidase IgA and IgG responses were significantly higher in cases with concomitant parasitic infection. Conclusion: Our data suggest that cholera patients develop age-distinct systemic and mucosal immune responses against sialidase. The stunted children have a lower anti-sialidase antibody response which may be associated with gut enteropathy and the neuraminidase plays an important role in augmented immune response in cholera patients infected with parasites.